Evaluasi Kepadatan Tanah Timbunan dengan Sand Cone - Faridz Moch. Ikbal; Athaya Zhafirah (Jurnal Konstruksi, 2022)
The construction of the new Cipanas Ring Road in Garut Regency aims to facilitate access to Cipanas attractions. One of the most important things in the construction of a new road is the density of the embankment obtained from the soil compaction process using heavy equipment. Soil density must meet the requirements, namely having a density degree value of more than 95%. If it does not meet the requirements, there will be damage to the landfill and in the long term it will damage the pavement structure above the ground. This study aims to determine whether the landfill on the New Cipanas Ring Road, Garut Regency meets the requirements or not. The method used is experimental testing in the field and in the laboratory. Testing the density of soil in the field using a sand cone refers to SNI 03-2828-1992, while testing the density of soil in the laboratory refers to SNI 1742-2008. Analysis of the results of soil density testing in the field and in the laboratory was carried out to obtain the dry unit weight value of the soil. The dry unit weight value of soil as a result of testing in the laboratory is used as a reference to determine the degree of soil density. The results of this study are that all the soil stockpile in Route A meets the requirements for soil density with a degree of density above 95%, while in Route B it does not meet the requirements for soil density. Piles of soil that meet the requirements for soil density can proceed to the next work and for piles of soil that do not meet the requirements, compaction is required.